2022
DOI: 10.3390/ijms23105513
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence on a Distinction between Aβ40 and Aβ42 Amyloids: Thioflavin T Binding Modes, Clustering Tendency, Degradation Resistance, and Cross-Seeding

Abstract: The relative abundance of two main Abeta-peptide types with different lengths, Aβ40 and Aβ42, determines the severity of the Alzheimer’s disease progression. However, the factors responsible for different behavior patterns of these peptides in the amyloidogenesis process remain unknown. In this comprehensive study, new evidence on Aβ40 and Aβ42 amyloid polymorphism was obtained using a wide range of experimental approaches, including custom-designed approaches. We have for the first time determined the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 92 publications
2
8
0
Order By: Relevance
“…13,21 Both fibrils and oligomeric aggregates of Aβ42 were reported to have the ability to crossseed Aβ40 monomers in a concentration-dependent manner, 13,29 which changes the morphology of Aβ40 fibrils and increases its stability and cytotoxicity. 30 As a hetero-seed, Aβ40 fibrils can also cross-seed Aβ42 monomers to rapidly aggregate. 21 Based on the important linkage between the crossinteraction of Aβ40−Aβ42 peptides and the AD progression, many research groups were devoted to reveal the molecular mechanisms of the cross-talk between the two peptides and attempted to resolve the structures of their co-aggregates.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,21 Both fibrils and oligomeric aggregates of Aβ42 were reported to have the ability to crossseed Aβ40 monomers in a concentration-dependent manner, 13,29 which changes the morphology of Aβ40 fibrils and increases its stability and cytotoxicity. 30 As a hetero-seed, Aβ40 fibrils can also cross-seed Aβ42 monomers to rapidly aggregate. 21 Based on the important linkage between the crossinteraction of Aβ40−Aβ42 peptides and the AD progression, many research groups were devoted to reveal the molecular mechanisms of the cross-talk between the two peptides and attempted to resolve the structures of their co-aggregates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The Chang’s group applied a single-molecule fluorescence resonance energy transfer technique and found that larger and substantially higher neurotoxic hetero-oligomers of Aβ40–Aβ42 were formed in cells compared to those formed from either peptide alone and suggested the synergistic effects between Aβ40 and Aβ42 peptides on altering both the morphology of the oligomers and their cytotoxicity. A large number of research studies reported the cross-seeding behavior between Aβ40 and Aβ42. , Both fibrils and oligomeric aggregates of Aβ42 were reported to have the ability to cross-seed Aβ40 monomers in a concentration-dependent manner, , which changes the morphology of Aβ40 fibrils and increases its stability and cytotoxicity . As a hetero-seed, Aβ40 fibrils can also cross-seed Aβ42 monomers to rapidly aggregate …”
Section: Introductionmentioning
confidence: 99%
“…In particular, as already noted, the authors of ref suggested that α-BC fibrils do not stain with ThT due to their structural features. Indeed, it was previously shown that the fluorescence quantum yield of ThT bound to amyloid fibrils with different structures can vary markedly (sometimes by orders of magnitude). In addition, refs , show the possibility of a decrease in ThT absorption and fluorescence values in extremely acidic and alkaline pH.…”
Section: Resultsmentioning
confidence: 99%
“…To transfer mature amyloids to other conditions, aggregates were precipitated by centrifugation (for 1–2 h at 18,000 rpm) and pellets were dissolved in deionized Milli-Q water or phosphate buffer (20 mM NaH 2 PO 4 /Na 2 HPO 4 ). Mature amyloids formed from Aβ40, Aβ42, and β2m using special protocols , were precipitated by centrifugation (for 1–2 h at 18,000 rpm) and pellets were dissolved in 20% acetic acid/100 mM NaCl (pH 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation